The Carbon Ion Energy Measurement in Pulse Filtered Cathodic Vacuum Arc Plasma Source for Study the Influence of Negative Substrate Bias Voltage - Buarabadthong , Phatthrawet; Pasaja, Nitisak (Burapha Science Journal, 2026)
This research is concerned with the process of measuring carbon ion energy from the pulse-filtered cathodic vacuum arc plasma source with the graphite as the cathode by using a retarding field ion energy analysis probe. To study the influence of a negative voltage biasing on carbon ion energy. The substrate was applied negative bias voltage from 0 to -80 V. To study the ion energy during the arc pulse plasma. The Time-resolved technique was used to measure carbon ion energy, with a time resolution of the order of 450 microseconds. The delay time for measuring the ion energy was adjusted from 0, 200, 400, 600, 800, and 1000 microseconds after arc ignition. The experimental result was found that the carbon ion energy in the arc plasma was dependent on substrate bias voltage, the carbon ion energy averages 20 eV when the substrate was biased at 0 V or grounded substrate. The carbon ion energy will be increased as the negative voltage bias to the substrate was increasing, where the carbon ion energy is 100 eV when the substrate was biased -80 V. The results show that the ion energy does not change with the arc pulse width and the ion energy is 20 eV at the grounded surface. The ion density changed with the arc pulse width, the ion density increased from 2.19x1016 m-3 for the first 450 microseconds up to 4.65x1016 m-3 for 450 to 1000 microseconds of the pulse width, and the ion density was decreased to zero for the end of the pulse width.